ETHNO-DEMOGRAPHICAL PROCESSES IN THE SOUTH CAUCASUS BY ADMINISTRATIVE UNITS (END OF THE 19TH CENTURY-BEGINNING OF THE 20TH CENTURY) - Boyajyan, A. (SUSh Scientific Proceedings, 2025)
The administrative-territorial and ethno-demographic changes taking place in the Russian Empire during the period under review were conditioned by the implementation and management of the autocracy's policy. The article aims to analyze the ethno-demographic processes of the population of the administrative-territorial units of the South Caucasus from an ethnogeographical perspective in the late 19th and early 20th centuries. The theoretical and methodological basis for the research was the primary sources published in different years on the topic under study, official statistical data, indicators of the results of the First All-Russian Census of 1897, scientific literature and other published factual materials on the ethnodemographics of the population of the region. The task is to identify and analyze the ethno-demographic trends of the administrative-territorial units of the South Caucasus, including the population size and reproduction, changes in national and religious composition. It is noteworthy that the region is distinguished by its ethnic diversity, with its characteristic socio-demographic, national preservation and ethnodemographic problems. It should be noted that the region is distinguished by interethnic and religious conflicts and clashes, which have been studied in depth by specialists, while new studies of ethno-demographic processes are few.